AN OVERVIEW TO THE NEW ERA IN EFFICIENT CROP MANAGEMENT: ARTIFICIAL INTELLIGENCE, MACHINE LEARNING, BIG DATA, BIOINFORMATICS, METAGENOMICS AND PRECISION AGRICULTURE - Ronald Oswaldo Villamar-Torres; Verónica Cristina Andrade Yucailla; Karen Rafaela Mayorga Morejon; Héctor Adonis Almeida Reyes; Seyed Mehdi Jazayeri (Journal of Animal and Plant Sciences, 2025)
The adoption of innovative technologies has revolutionized agriculture, ushering in a new era of efficient crop management. Advanced tools, including Artificial Intelligence (AI), Machine Learning (ML), Big Data, Bioinformatics, Metagenomics, and Precision Agriculture, are transforming traditional farming practices. AI and ML algorithms analyze vast amounts of agricultural data, generating valuable insights for farmers. These insights support data-driven decisions related to planting schedules, irrigation, pest and disease management, and fertilizer application, enhancing productivity and profitability. Big Data analytics aggregates and processes data from various sources such as satellite imagery, drones, sensors, and farm machinery. This allows farmers to monitor crops remotely, detect anomalies, and identify areas for improvement in real time, optimizing resource allocation and reducing waste. Bioinformatics and Metagenomics leverage genomic data to develop genetically modified crops that are more resilient to pests, diseases, and environmental stressors, enhancing both yield and quality. Precision Agriculture employs technologies like GPS, drones, and Internet of Things (IoT) devices to create detailed maps of fields. This enables precise and targeted resource application, reducing waste and minimizing environmental impact. The synergistic combination of these technologies represents a paradigm shift in agriculture, empowering farmers to optimize crop management, increase food production, ensure food security, and contribute to sustainable practices. As agriculture continues to innovate, it will play a crucial role in addressing global challenges such as population growth, resource scarcity, climate change and environmental sustainability. The future of farming lies in connectivity and data-driven solutions.
Keywords: Geographic Information Systems (GIS); Internet of Things (IoT); Next Generation Sequencing (NGS)